DNGR1-mediated deletion of A20/Tnfaip3 in dendritic cells alters T and B-cell homeostasis and promotes autoimmune liver pathology. (August 2019) - Das, Tridib; Bergen, Ingrid M.; Koudstaal, Thomas; van Hulst, Jennifer A.C.; van Loo, Geert; Boonstra, André; Vanwolleghem, Thomas; Leung, Patrick S.C.; Gershwin, M. Eric; Hendriks, Rudi W.; Kool, Mirjam
Abstract: Dendritic cells (DCs) are central regulators of tolerance versus immunity. The outcome depends amongst others on DC subset and activation status. Whereas CD11b + type 2 conventional DCs (cDC2s) initiate proinflammatory helper T (Th)-cell responses, CD103 + cDC1s are crucial for regulatory T-cell (Treg) induction and CD8 + T-cell activation. DC activation is controlled by the transcription factor NF-κB. Ablation of A20/Tnfaip3, a critical regulator of NF-κB activation, in DCs leads to constitutive DC activation and development of systemic autoimmunity. We hypothesized that the activation status of cDCs controls the development of autoimmunity. To target cDCs, DNGR1( Clec9a )-cre-mediated excision of A20/Tnfaip3 was used through generation of Tnfaip3 fl/fl x Clec9a +/cre ( Tnfaip3 DNGR1−KO ) mice. Immune cell activation was evaluated at 31-weeks of age. We found that DNGR1-cre-mediated deletion of A20/Tnfaip3 resulted in liver pathology characterized by inflammatory infiltrates adjacent to the portal triads. Both cDC subsets as well as monocyte-derived DCs (moDCs) in Tnfaip3 DNGR1−KO livers harbored an activated phenotype. Specifically, the costimulatory molecule CD40 in liver cDCs and moDCs was regulated by A20/Tnfaip3 expression. Livers from Tnfaip3 DNGR1−KO mice had augmented proportions of Th1, Th17, Treg, and follicular Th (Tfh)-cells compared to control mice, accompanied by an increase in IgA-producing plasma cells. Serum IgA from Tnfaip3 DNGR1−KO mice recognized self-proteins, specifically cytoplasmic proteins in liver periportal regions. These data show that enhanced activation of cDCs and moDCs, due to A20/Tnfaip3 ablation, promotes the development of organ-specific autoimmunity but not systemic autoimmunity. This model could be useful to examine the pathobiological processes contributing to autoimmune liver diseases. Highlights: Tnfaip3 is a crucial negative feedback enzyme of proinflammatory NF-κB activation. Deletion of Tnfaip3 by DNGR1-cre activates conventional and monocyte-derived DCs. Tnfaip3 DNGR1−KO mice spontaneously develop chronic liver inflammation. Liver Th1-cells, Th17-cells, and plasma cells are increased in Tnfaip3 DNGR1−KO mice. Tnfaip3 DNGR1−KO mice develop IgA antibodies recognizing liver periportal antigens.